2002
DOI: 10.1007/s10350-004-6118-z
|View full text |Cite
|
Sign up to set email alerts
|

Strength-Duration Testing of the External Anal Sphincter in Females with Anorectal Dysfunction

Abstract: The strength-duration test significantly correlates with the established measures of external anal sphincter function and its innervation. Therefore, this simple test appears to provide a simple measure of external anal sphincter denervation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
0
8
1
Order By: Relevance
“…Although there was a high incidence (32%) of anterior EAS defects detected on endoanal ultrasound, this cannot fully explain our results, as there was no significant difference in energy requirement between patients with intact EAS and those with defects in this stimulus position. Although no correlation was seen between the SDT at 3 o'clock and the left PNTML, our study size was smaller than previous research into the SDT [4,5] and no significant difference was identified in the SDCs produced at the 3 and 9 o'clock positions. These points closely correspond to where the pudendal nerves enter the EAS.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Although there was a high incidence (32%) of anterior EAS defects detected on endoanal ultrasound, this cannot fully explain our results, as there was no significant difference in energy requirement between patients with intact EAS and those with defects in this stimulus position. Although no correlation was seen between the SDT at 3 o'clock and the left PNTML, our study size was smaller than previous research into the SDT [4,5] and no significant difference was identified in the SDCs produced at the 3 and 9 o'clock positions. These points closely correspond to where the pudendal nerves enter the EAS.…”
Section: Discussioncontrasting
confidence: 72%
“…However, six had to withdraw due to unforeseen circumstances. More patients stopped the test because of pain than has been previously reported [4,5], though the majority of those women were able to tolerate the SDT at least once. On the whole patients found the test acceptable.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A detailed medical and obstetric history was obtained from the patients. Anal manometry, PNTML and EAUS [7] have been previously described and were performed by a trained technician.…”
Section: Study Groupmentioning
confidence: 99%
“…The two groups had entirely different SDCs and it suggested that the test might have a useful role in the assessment of EAS function. Subsequently, we [7] identified weak but appropriate correlations between the SDT and other physiological measurements of EAS function.…”
Section: Introductionmentioning
confidence: 96%